B cells and CD22 are dispensable for the immediate antiinflammatory activity of intravenous immunoglobulins in vivo - Schwab, Inessa; Seeling, Michaela; Biburger, Markus; Aschermann, Susanne; Nitschke, Lars; Nimmerjahn, Falk (European journal of immunology, 2012)
Intravenous immunoglobulins (IVIgs) efficiently suppress a variety of autoimmune diseases. Over the past few years several potential mechanisms underlying this antiinflammatory activity have become apparent. Among these, terminal sialic acid residues in the sugar moiety of the immunoglobulin G constant fragment have been shown to be critical for the antiinflammatory activity of IVIgs in models of rheumatoid arthritis and immunothrombocytopenia (ITP). More recently, B cells and the sialic acid-binding protein CD22 were suggested to be involved in this IVIg-dependent immunomodulatory pathway. To study whether B cells are directly involved in IVIg-mediated suppression of acute autoimmune diseases, we tested the activity of IVIgs in mice deficient in B cells or CD22. We show that neither B cells nor CD22 are critical for the immediate antiinflammatory activity of IVIgs in mouse models of rheumatoid arthritis and ITP.